Whole-organ isolation approach as a basis for tissue-specific analyses in Schistosoma mansoni - Hahnel, Steffen; Lu, Zhigang; Wilson, R. Alan; Grevelding, Christoph G.; Quack, Thomas; Justus Liebig University Giessen (My University, 2013)
As a neglected disease, schistosomiasis is still an enormous problem in the tropics and subtropics. Since the 1980s, Praziquantel (PZQ) has been the drug of choice but can be anticipated to lose efficacy in the future due to emerging resistance. Alternative drugs or efficient vaccines are still lacking, strengthening the need for the discovery of novel strategies and targets for combating schistosomiasis. One avenue is to understand the unique reproductive biology of this trematode in more detail. Sexual maturation of the adult female depends on a constant pairing with the male. This is a crucial prerequisite for the differentiation of the female reproductive organs such as the vitellarium and ovary, and consequently for the production of mature eggs. These are needed for life-cycle maintenance, but they also cause pathogenesis. With respect to adult males, the production of mature sperm is essential for fertilisation and life-cycle progression. In our study we present a convenient and inexpensive method to isolate reproductive tissues from adult schistosomes in high amounts and purity, representing a source for gonad-specific RNA and protein, which will serve for future sub-transcriptome and -proteome studies helping to characterise genes, or to unravel differentiation programs in schistosome gonads. Beyond that, isolated organs may be useful for approaches to establish cell cultures, desperately needed in the post-genomic era.
Keywords: ddc:570